Applicability of an abbreviated version of the Child-OIDP inventory among primary schoolchildren in Tanzania - Mtaya Matilda; Åstrøm Anne N; Tsakos Georgios (Health and Quality of Life Outcomes, 2007)
Abstract Background There is a need for studies evaluating oral health related quality of life (OHRQoL) of children in developing countries. Aim to assess the psychometric properties, prevalence and perceived causes of the child version of oral impact on daily performance inventory (Child-OIDP) among school children in two socio-demographically different districts of Tanzania. Socio-behavioral and clinical correlates of children's OHRQoL were also investigated. Method One thousand six hundred and one children (mean age 13 yr, 60.5% girls) attending 16 (urban and rural) primary schools in Kinondoni and Temeke districts completed a survey instrument in face to face interviews and participated in a full mouth clinical examination. The survey instrument was designed to measure a Kiswahili translated and culturally adapted Child-OIDP frequency score, global oral health indicators and socio-demographic factors. Results The Kiswahili version of the Child-OIDP inventory preserved the overall concept of the original English version and revealed good reliability in terms of Cronbach's alpha coefficient of 0.77 (Kinondoni: 0.62, Temeke: 0.76). Weighted Kappa scores from a test-retest were 1.0 and 0.8 in Kinondoni and Temeke, respectively. Validity was supported in that the OIDP scores varied systematically and in the expected direction with self-reported oral health measures and socio-behavioral indicators. Confirmatory factor analyses, CFA, confirmed three dimensions identified initially by Principle Component Analysis within the OIDP item pool. A total of 28.6% of the participants had at least one oral impact. The area specific rates for Kinondoni and Temeke were 18.5% and 45.5%. The most frequently reported impacts were problems eating and cleaning teeth, and the most frequently reported cause of impacts were toothache, ulcer in mouth and position of teeth. Conclusion This study showed that the Kiswahili version of the Child-OIDP was applicable for use among schoolchildren in Tanzania.